2005
DOI: 10.1007/s00415-005-0815-y
|View full text |Cite
|
Sign up to set email alerts
|

Gastric emptying after semi–solid food in multiple system atrophy and Parkinson disease

Abstract: Our results suggest that patients with MSA have GE rates similar to those of patients with PD, but slower than healthy age matched individuals. It remains to be investigated whether gastrointestinal dysfunction in MSA is related to both brain and peripheral pathology, as is presumed for PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 19 publications
1
30
1
2
Order By: Relevance
“…90%) compared to other dopamine agonists (10). In contrast, the pharmacokinetics of oral L-dopa largely depends on various factors, such as gastric emptying, which is known to be slow in MSA patients (11). This results in considerable variability among patients (12).…”
Section: Discussionmentioning
confidence: 98%
“…90%) compared to other dopamine agonists (10). In contrast, the pharmacokinetics of oral L-dopa largely depends on various factors, such as gastric emptying, which is known to be slow in MSA patients (11). This results in considerable variability among patients (12).…”
Section: Discussionmentioning
confidence: 98%
“…Among lower gastrointestinal symptoms, constipation is a common feature and a change in bowel habits suggests autonomic involvement of the lower gut [12]. Patients with MSA sometimes complain of upper gastrointestinal symptoms [2]. Gastrointestinal symptoms may be associated with reduced gastrointestinal motility due to autonomic nervous system dysfunction of MSA [2].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with MSA sometimes complain of upper gastrointestinal symptoms [2]. Gastrointestinal symptoms may be associated with reduced gastrointestinal motility due to autonomic nervous system dysfunction of MSA [2]. The previous study suggested that GE of patients with MSA was slower than the control [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations